Hubungan Perilaku Asertif Dengan Kenakalan Remaja Pada Siswa - Elvira (ILIN Institute Makassar, 2022)
This research aims to determine (l) the relationship between assertive behavior and delinquency in class XI teenagers at SMA Negeri 2 Biau. The data analysis techniques used are descriptive analysis and product moment correlation analysis. Based on research, it is known that the majority of respondents' assertive behavior is in the high category, namely 73.95%. Most of the respondents' juvenile delinquency was included in the moderate category, 64.71%. The results of the correlation analysis obtained a correlation coefficient of -0.211. The results of the correlation test show that the rxy obtained is -0.211, while in the r table with N = 119 it is 0.176. Because the calculated r value > r table (-0.211 > 0.176) there is a negative relationship between certifying behavior and juvenile delinquency. The effective contribution of the assertive variable is 4.45% to juvenile delinquency among class XI students at SMA Negeri 2 Biau. Penelitian ini bertujuan untuk mengetahui (l) Hubungan perilaku asertif dengan kenakalan remaja kelas XI di SMA Negeri 2 Biau. Teknik analisis data yang digunakan adalah analisis deskriptif dan analisis korelasi product moment. Berdasarkan penelitian diketahui bahwa sebagian besar perilaku asertif responden termasuk kategori tinggi yaitu 73,95%. Sebagian besar kenakalan remaja responden yang termasuk dalam kategori cukup 64,71%. Hasil analisis korelasi diperoleh besarnya koefisien korelasi sebesar -0,211. Hasil uji korelasi menunjukkan bahwa rxy yang diperoleh sebesar -0,211 sedangkan pada r tabel dengan N =119 sebesar 0,176. Karena nilai r hitung > r tabel (-0,211 > 0,176) maka terdapat hubungan negatif antara perilaku sertif dengan kenakalan remaja. Sumbangan efektif variabel asertif sebesar 4,45% terhadap kenakalan remaja pada siswa kelas XI SMA Negeri 2 Biau.